The last phase of armed resistance ( Šiauliai region) - Norbutas, Simonas (Genocidas ir rezistencija, 2002)
According to the MGB data, in the spring of 1952 there were still 142 partisan structures in Lithuania, with roughly 900 fighters in their ranks, although they were no longer a well–organised force they had used to be. For security reasons, partisans operated in small groups, which often lost contact not only with the command centres but also with each other at the level of their immediate subordination. Arrests and mass deportations (in the autumn of 1951 and spring of 1952, some additional 20,000 people were deported from Lithuania) led to a sharp drop in supporters. A dense network of agents was in place (372 agents were recruited in the first half of 1952 alone), following partisans’ every move. This article describes how the MGB suppressed of what was left of the partisan movement in the region.